PENGARUH KEPRIBADIAN PROAKTIF DAN POLA PIKIR KEWIRAUSAHAAN TERHADAP KEBERLANJUTAN BISNIS PADA USAHA LAS KETOK DI KECAMATAN MEDAN DENAI - RUDY; CARISSA GONATA (LP2MTBM MAKARIOZ, 2021)
Medan City is one of the service cities, where there are various kinds of businesses in Medan City, ranging from culinary businesses, businesses in the banking sector, to ketok welding services located in various areas of Medan City, especially in the Medan Denai area, where the development of this ketok welding business has not increased significantly, Besides the profits obtained are not optimal, the las ketok business in Medan cannot develop because business owners tend not to be proactive in analyzing how efforts are made so that their business can develop, so that courage in deciding things cannot be done because business owners also do not have the mindset of being an entrepreneur, because business owners open businesses only to meet their needs in life. This can be seen during approximately 2019-2020 the number of las ketok entrepreneurs in Medan Denai District has decreased from the original 60 entrepreneurs to 35 people who opened their businesses in Medan Denai District. TThis study aims to find out how the influence of the proactive personality of ketok welding entrepreneurs in Medan Denai District and the entrepreneurial mindset of ketok welding entrepreneurs in Medan Denai District on the sustainability of the las ketok business in Medan Denai District. The total population in this study amounted to 35 people who were ketok welding entrepreneurs in Medan Denai District, where the sampling technique used a saturated sample technique with a total sample of 35 ketok welding entrepreneurs in Medan Denai District. The results of the study can be concluded that simultaneously and partially the variables of the proactive personality of las ketok entrepreneurs in Medan Denai District and the entrepreneurial mindset of las ketok entrepreneurs in Medan Denai District affect the sustainability of the las ketok business in Medan Denai District